Mitigation of 3-monochloropropane-1,2-diol esters and glycidyl esters in refined palm oil: a new and optimized approach - Hew, Khai Shin; Khor, Yih Phing; Tan, Tai Boon; Mat Yusoff, Masni; Lai, Oi Ming; Asis, Ahmad Jaril; Alharthi, Fahad A.; Nehdi, Imededdine Arbi; Tan, Chin Ping (Elsevier, 2021)
Refined, bleached and deodorized palm oil (RBDPO) is reported to contain high amount of 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE) due to high-temperature deodorization step and rich in organochlorines. Therefore, a new palm oil refining process was developed to mitigate this problem. The conventional physical refining process was modified and optimized using response surface methodology with selected processing parameters (water and acid dosages, pre-treatment and deodorization temperatures and deodorization duration). Formation of esters in oil during refining was modelled, and a new refining approach which had been optimized and validated was developed. The new method achieved significant reduction in ester contents (78% reduction for 3-MCPDE, 53% reduction for GE; p < 0.05), with free fatty acid content and color maintained at < 1.0% and < 3.0 R. Similar mitigation effect was confirmed by testing the new refining approach with different grades of crude palm oil.